2000
DOI: 10.1088/0953-8984/13/3/312
|View full text |Cite
|
Sign up to set email alerts
|

Formation of silver particles and periodic precipitate layers in silicate glass induced by thermally assisted hydrogen permeation

Abstract: Nanoscale silver particles embedded in sodium silicate glass were produced by Na/Ag ion exchange and subsequent thermal treatment in a hydrogen atmosphere. Their structure and spatial distribution were studied by conventional and high-resolution electron microscopy (HREM). Two different mechanisms of particle formation could be identified: (i) reduction of ionic silver by hydrogen and formation of mostly defective particles (twinned) within a near-surface region; and (ii) formation of single-crystalline partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…Given an additional process related to the kinetics of the formation of silver particles from reduced silver ions, the case can be hardly subjected to a qualitative analysis, and, to understand the behavior of the obtained dependences τ(x), one should turn to the problem as a whole, that is, to the problem of multicomponent diffusion with sinks. This problem was solved in general, see for example [15], and it was found that, in the course of the process of silver particle formation, depth distributions of the size and concentration of the particles could have a maximum and even form periodic layers [16]. Definitely, this leads to an uncertain depth and lateral distribution of the absorption coefficient changing in time, which, in turn, unpredictably influences the shape of τ(x); essentially, in the case of short heat treatments in H 2 atmosphere, that is, when the process of nanoparticle formation is not accomplished (like curve 1 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given an additional process related to the kinetics of the formation of silver particles from reduced silver ions, the case can be hardly subjected to a qualitative analysis, and, to understand the behavior of the obtained dependences τ(x), one should turn to the problem as a whole, that is, to the problem of multicomponent diffusion with sinks. This problem was solved in general, see for example [15], and it was found that, in the course of the process of silver particle formation, depth distributions of the size and concentration of the particles could have a maximum and even form periodic layers [16]. Definitely, this leads to an uncertain depth and lateral distribution of the absorption coefficient changing in time, which, in turn, unpredictably influences the shape of τ(x); essentially, in the case of short heat treatments in H 2 atmosphere, that is, when the process of nanoparticle formation is not accomplished (like curve 1 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a variety of modifier oxides were introduced into the glass network by different routs like ion exchange [22,23], ion implantation [24], irradiation-assisted processing, i.e. ion [25], electron [18] and laser [26] irradiation, sol-gel synthesis [27], reducing atmosphere treatment [28] or co-sputtering of metal-glass target [29].…”
Section: Introductionmentioning
confidence: 99%
“…Platinum nanoparticles have been attached to the surface of a glass slide using a chemical reduction method, 18 Qiu et al reported the photoreduction of Ag + ions to Ag atoms in a silicate glass by focusing 120 fs laser pulses 19 and Mohr et al produced nanoscale silver particles by Na/Ag ion exchange and subsequent thermal treatment in a hydrogen atmosphere. 20 However, these techniques and conventional physical vapor deposition (PVD) and chemical vapor deposition (CVD) techniques are expensive and require specialized laboratory technicians. 21,22 On the other hand, the immobilization of nanoparticles through wetchemistry approaches is low cost, but the possibility of surface contamination by reducing agents or chemisorbed stabilizers must be overcome.…”
Section: Introductionmentioning
confidence: 99%